The Effect of Traditional Games Gobak Sodor and Bentengan to Improvement Physical Fitness Students Elementary School - Agus Riyadi; Samsudin; Iman Sulaiman (Gladi : Jurnal Ilmu Keolahragaan, 2021)
This study aims to determine the effect of traditional Gobak Sodor and Bentengan game training on improving the physical fitness of grade V and VI-grade students of Sukagumiwang III Elementary School. The research method used in this research is an experimental method through pretest and posttest to determine the level of physical fitness. The population of this research was students consisting of 18 students of class V and 18 students of class VI with a total population of 36 people. While the sample was 30 people, the sampling was purposive namely male students in grades V and VI. The analysis technique used is the average test with the t-test formula. The results of hypothesis testing indicate that there is an effect of traditional games on increasing fitness. The results of descriptive calculations show that the initial test average data is 14.20%, the average final test is 20.60%, and there is an increase of 6.40% for class V. Whereas for class VI the average initial test is 14.60%, final test average. was 21.50% and an increase of 6.93%. The results of this study indicate that the traditional Bentengan game training is more influential than the traditional Gobak Sodor game, although the two matches have a significant effect on improving the physical fitness of students in grades V and VI of Sukagumiwang III Elementary School, Sukagumiwang District, Indramayu Regency.